(3QSGdI aj GdJhMjOs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdPi CQSd QShdg HGdgOi hOjf GdMb CeG HYO agPG EYJbGO GdaQbI GdfGLjI GdefUhQI Edi bjGe GdSGYI Cgd GdSfI hGdLeGYI s
(3BNQgG (B:s
(3hdG ef NPdge MJi Jbhe GdSGYI afSFd Gddg Ef jLYdfG efge hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds